Model Pendidikan Karakter Anak Usia Prasekolah Berbasis Metode Dongeng pada Taman Kanak-Kanak di Kota Kendari - Marsia Sumule Genggong; Asrul Jaya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
The purpose of this study is to determine how the delivery of a fairy tale that can be used as the basis of the character building education of preschool children in kindergarten in Kendari. The study used the qualitative descriptive method that describes a particular social situation performed by actors in the interactions. Researchers conducted data collection through in-depth interviews to the children who were treated by story telling at home by their parents and their kindergarten by their teachers. The researchers observed, check the information validity, and did some library research to complete the data through books, magazine, paper article, and photos documentation that related to the research object. The results of this study indicate that the fairy tale and the presentation (story telling) is still not a priority in doing in kindergarten because of various constraints, especially on the lack of teachers' creativity, participation, and concern of parents in the attempt of character building. Storytelling is considered as a good medium for the development of children's character. Story telling could be effective both presented with or without properties. Keywords: story telling, character, preschool-age children